The Anglican Doctrine of the Visible Church - Gatiss, Lee (2020)
This article examines what the Church of England's historic Thirty-nine Articles of Religion actually mean in context when they define the visible church as "a congregation of faithful men in which the pure Word of God is preached, and the sacraments be duly ministered according to Christ's ordinance in all those things that of necessity are requisite to the same." The article clarifies the meaning of the words "a congregation" here in their historical and polemical context during the Reformation, giving this significant attention for the first time in print, in order to correct common evangelical mis-readings and misappropriations of Article 19. It also unpacks the Anglican view of the marks of the church against the confessional divides of the 16th century, to locate this Article in its Reformed Protestant context against Rome. It outlines ten challenges which a properly understood Anglican ecclesiology presents for evangelicals today.
Keywords: Anglican Communion; Anglican; Church; Church of England; Congregationalism; Congregationalism; Episcopacy; Reformation; Thirty-nine Articles; Church; Congregation; Discipline; Ecclesiology; Episcopacy; Polity